Ability to Write Scientific Work for Class XI Students of SMA Negeri 4 Sidenreng Rappang Based on Direct Observation - Kamal Podding; Musfiratul Soleha (Universitas Muhammadiyah Enrekang, 2023)
This research aims to determine the ability of class XI students at SMA Negeri 4 Sidenreng Rappang in writing scientific papers based on direct observation. This study used descriptive qualitative method. The data source was obtained from class XI students of SMA Negeri 2 Sidenreng Rappang. totaling 40 students taken as a sample of 20% of 208 students. Data was obtained by means of participant observation, documentation, and written tests and then processed using qualitative descriptive analysis techniques. The data collected in this research will be analyzed using percentage variance analysis techniques and processed by creating a list of raw scores, while for standardization purposes, measuring each student's abilities is carried out by transforming the raw scores into scores on a scale of 10 - 100. Next, determine the percentage of student mastery of the material being tested with criteria of 85% and above with the lowest score being 65 on a scale of 10 -100. The results of this research show that the frequency and percentage of class %) who scored less than 65.student at SMA Negeri 4 Sidenreng Rappang able to write scientific papers, because they have achieved the specified target, namely 85% for a score of 65 and above on the 10-100 assessment scale.